PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA GURU PADA SEKOLAH GLOBAL MANDIRI - Herni Pujiati (Jurnal Manajemen Bisnis Krisnadwipayana, 2016)
The tittle of this research is “ The influence of leadership analysis and the compensation to teacher performance in global Mandiri School “ The aim of this research is to know and to proof how big is the influence between leadership and teacher performance in Global Mandiri School. This research bases on a survey research method by using correlation, predictive and explanatory approach. By taking 100 samples of people who are teacher. To solve the problems by analyzing and testing the link and the influence between independent variable and dependent variable uses kaulistik models through regression analysis based on SPSS 14.0